Self And Opposition : a Theory of Self. - Hoffman, Piotr (Marquette studies in philosophy., 2017)
The author argues that the individual and continuing self emerges from human interactions and that the interactions at issue are the relations of opposition. The argument then proceeds to show how the same relations of opposition constitute the self as endowed with free will.